NĠKÂH VE TALÂK’TA ġAHĠTLĠK - Kudaynetov, Said Ali (Scientific Journal of Faculty of Theology, 2015)
The issue about a testimony on Marriage and Divorce are brought into attention. This issue was examined through two Ayats. Firstly, it was focused on the Marriage testimony, and the short information about the conditions of testimony was given due to the views of the Imams from the different Islamic doctrines. Moreover it was touched about the witnessing of the women. The issue about a Divorce Testimony was also elaborated. As a result, it was underlined that the Marriage Testimony comparing with Testimony during the Divorce is obligation procedure (wadjib), and the witnessing of the Divorce is a desirable action (mandub).